The Effect of Thyroid Hormone, Prostaglandin E2, and Calcium Gluconate on Orthodontic Tooth Movement and Root Resorption in Rats - Seifi, Massoud (J Dent (Shiraz), 2015)
STATEMENT OF THE PROBLEM: A major objective of investigators is to clarify the role of metabolites in achievement of maximum tooth movement with minimal root damage during orthodontic tooth movement (OTM). PURPOSE: The aim of this study was to determine the effect of administration of thyroid hormone, prostaglandin E2, and calcium on orthodontic tooth movement and root resorption in rats. MATERIALS AND METHOD: Sixty four male Wistar rats were randomly divided into 8 groups of eight rats each: 1- 20µg/kg thyroxine was injected in traperitoneally after installation of the orthodontic appliance.  2- 0.1 ml of 1 mg/ml prostaglandin E2 was injected submucosally.  3- 10% (200 mg/kg) calcium gluconate was injected.  4- Prostaglandin E2 was injected submucosally and 10% calcium was injected intraperitoneally.  5- Thyroxine was injected intraperitoneally and prostaglandin E2 was injected submucosally.  6- 20µg/kg thyroxine with calcium was injected. 7- Prostaglandin E2 was injected submucosally with calcium and thyroxine.  8- Distilled water was used in control group. The orthodontic appliances comprised of a NiTi closed coil were posteriorly connected to the right first molar and anteriorly to the upper right incisor. OTM was measured with a feeler gauge. The mid-mesial root of the first molar and the adjacent tissues were histologically evaluated. The Data were analyzed by one-way ANOVA and Student-Newman-Keuls test. RESULTS: The highest mean OTM was observed in the thyroxine and prostaglandin E2 group (Mean±SD = 0.7375±0.1359 mm) that was significantly different (p< 0.05). A significant difference (p< 0.05) in root resorption was observed between the prostaglandin E2 (0.0192±0.0198 mm(2)) and the other groups. CONCLUSION: It seems that the combination of thyroxine and prostaglandin E2, with a synergistic effect, would decrease the root resorption and increase the rate of orthodontic tooth movement in rats.